The evaluation of larvae of Musca Domestica (common house fly) as protein source for boiler production - Pretorius, Quinton (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2011.